A CRITICAL EXAMINATION TOWARDS THE ISLAMIC DISCOURSE ON â€œLIMITED LIABILITYâ€ (UUM Journal of Legal Studies, 2020)
The concept of limited liability has been a very important component of the development of the global economy. However, while limited liability is currently a reality all over the world including in the Islamic nations, it is not without discourse among the Muslim jurists. The debate mainly revolves around two core issues. The first issue is the concern of some jurists that the only acknowledged legal entity in Islamic law are natural persons, and that legal persons (like limited liability corporations) are ‘fictitious’. The second issue is concerning how the owners of the limited liability companies have rights to residual profits of the company, but do not bear the liability towards the debt when insolvency occurs. Some jurists are concerned because the Shari‘ah dictates that paying debts is a very serious matter. Using a literature research method, this article will critically examine the debate between the jurists especially in the two issues mentioned earlier and determine which argument is stronger. It is found that, in the end, establishing a legal entity other than natural persons as well as barring company owners from debt liability are very hard to justify under the Shari‘ah. However, given the status-quo construct of global economics, not utilizing limited liabilities may cause devastating economic repercussions. Therefore, a new model of corporation might need to be researched and explored in order to suit the necessities of the economy as well as being consistent with the Shari‘ah.